Automating case definitions using literature-based reasoning - Botsis, T.; Ball, R. (Applied Clinical Informatics, 2013)
Background: Establishing a Case Definition (CDef) is a first step in many epidemiological, clinical, surveillance, and research activities. The application of CDefs still relies on manual steps and this is a major source of inefficiency in surveillance and research.Objective: Describe the need and propose an approach for automating the useful representation of CDefs for medical conditions.Methods: We translated the existing Brighton Collaboration CDef for anaphylaxis by mostly relying on the identification of synonyms for the criteria of the CDef using the NLM MetaMap tool. We also generated a CDef for the same condition using all the related PubMed abstracts, processing them with a text mining tool, and further treating the synonyms with the above strategy. The co-occur-rence of the anaphylaxis and any other medical term within the same sentence of the abstracts supported the construction of a large semantic network. The ‘islands’ algorithm reduced the network and revealed its densest region including the nodes that were used to represent the key criteria of the CDef. We evaluated the ability of the “translated” and the “generated” CDef to classify a set of 6034 H1N1 reports for anaphylaxis using two similarity approaches and comparing them with our previous semi-automated classification approach.Results: Overall classification performance across approaches to producing CDefs was similar, with the generated CDef and vector space model with cosine similarity having the highest accuracy (0.825±0.003) and the semi-automated approach and vector space model with cosine similarity having the highest recall (0.809±0.042). Precision was low for all approaches.Conclusion: The useful representation of CDefs is a complicated task but potentially offers substantial gains in efficiency to support safety and clinical surveillance.Citation: Botsis T, Ball R. Automating case definitions using literature-based reasoning. Appl Clin Inf 2013; 4: 515–527http://dx.doi.org/10.4338/ACI-2013-04-RA-0028
Keywords: Case definition; safety surveillance; semantic networks; literature-based reasoning; anaphylaxis; similarity